2014
DOI: 10.1088/0967-3334/35/4/687
|View full text |Cite
|
Sign up to set email alerts
|

A mock circulation model for cardiovascular device evaluation

Abstract: The aim of this study was to develop an integrated mock circulation system that functions in a physiological manner for testing cardiovascular devices under well-controlled circumstances. In contrast to previously reported mock loops, the model includes a systemic, pulmonary, and coronary circulation, an elaborate heart contraction model, and a realistic heart rate control model. The behavior of the presented system was tested in response to changes in left ventricular contractile states, loading conditions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…A high peak in the initial diastolic transmitral pressure drop is measured in the tests (up to 45 mmHg). This is often observed in tests performed on hydro-mechanical pulse duplicators,16,28,29,48,53,55 and could be due to the non-physiological ventricular compliance, which may determine steeper flow waves and higher pressure gradients associated with early passive filling during ventricular relaxation. The calculated EOA well reflected the variation in the area of the implantation annulus, varying proportionally.…”
Section: Discussionmentioning
confidence: 98%
“…A high peak in the initial diastolic transmitral pressure drop is measured in the tests (up to 45 mmHg). This is often observed in tests performed on hydro-mechanical pulse duplicators,16,28,29,48,53,55 and could be due to the non-physiological ventricular compliance, which may determine steeper flow waves and higher pressure gradients associated with early passive filling during ventricular relaxation. The calculated EOA well reflected the variation in the area of the implantation annulus, varying proportionally.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Miyazaki et al and Abdelghani et al, in an experimental study, reported excellent agreement between VD and regurgitation fraction evaluated in an in vitro setting. 11,12,21,22 Therefore, VD assessment (LVOT-AR) may play a central role in TAVI procedural guidance in the context of the minimalist TAVI approach. We believe that this intra-procedural direct comparison between the 2 modalities would facilitate the adoption of VD assessment into clinical practice.…”
Section: Clinical Impact Of Angiographic Post-tavi Ar (Lvot-ar)mentioning
confidence: 99%
“…To simulate physiologically realistic pulsatile flow, a dedicated pumping system is used in these experiments. This can either be a mock loop representing the full circulatory system [8,9], or a pump that reproduces a waveform measured locally in-vivo [4,5,6,7,12].…”
Section: Introductionmentioning
confidence: 99%